2014
DOI: 10.11648/j.sjc.20140205.11
|View full text |Cite
|
Sign up to set email alerts
|

Facile New Syntheses of Substituted Benzhydryl Derivatives Using Trichloroacetimidate C-C Bond Formation Method

Abstract: An improved syntheses of substituted benzhydryl derivatives has been developed. This facile two-step procedure involves CC bond formation from O-diphenylmethyltrichloroacetimidate and C-nucleophiles in the presence of TMSOTf. The C-nucleophiles include arenes, alkenes, alkene silylated C-nucleophiles and trimethylsiloxy alkenes to give a series substituted benzhydryl derivatives in excellent yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
(41 reference statements)
0
5
0
Order By: Relevance
“…Herein, we report the synthesis of a series of compounds based on structure modification of the model methyl 3-(4-chlorophenyl)-3-hydroxy-2,2-dimethylpropanoate Trichloroacetimidateand acetate C-C coupling proved to be excellent methods for structure modifications of alcohols. [14][15][16][17][18] These methods are related to transform hydroxyl group substrates into the appropriate trichloroacetimidate or acetate excellentleaving groups by the reaction with trichloroacetonitrile or acetic anhydride, respectively. The successive addition of C-nucleophiles mainly activated arenes, allyltrimethylsilaneand trimethylsiloxy alkenesto the active trichloroacetimidate or acetate intermediates in the presence of Lewis acid gave the desired products.…”
Section: Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Herein, we report the synthesis of a series of compounds based on structure modification of the model methyl 3-(4-chlorophenyl)-3-hydroxy-2,2-dimethylpropanoate Trichloroacetimidateand acetate C-C coupling proved to be excellent methods for structure modifications of alcohols. [14][15][16][17][18] These methods are related to transform hydroxyl group substrates into the appropriate trichloroacetimidate or acetate excellentleaving groups by the reaction with trichloroacetonitrile or acetic anhydride, respectively. The successive addition of C-nucleophiles mainly activated arenes, allyltrimethylsilaneand trimethylsiloxy alkenesto the active trichloroacetimidate or acetate intermediates in the presence of Lewis acid gave the desired products.…”
Section: Chemistrymentioning
confidence: 99%
“…The successive addition of C-nucleophiles mainly activated arenes, allyltrimethylsilaneand trimethylsiloxy alkenesto the active trichloroacetimidate or acetate intermediates in the presence of Lewis acid gave the desired products. [14][15][16][17][18] We find it interesting to apply the trichloroacetimidate and acetate coupling methods in the structure modification of methyl Comparing the efficiency of both C-C coupling methods according toreaction time and % of yield, results showed that, although, all compounds were prepared in good yields, there was a slight improvement in the % of yield and in the reaction time (monitored by TLC) using trichloroacetimidate method.…”
Section: Chemistrymentioning
confidence: 99%
“…Trichloroacetimidate and acetate C-C coupling proved to be excellent methods for structure modications of alcohols. [14][15][16][17][18] These methods are related to transform hydroxyl group substrates into the appropriate trichloroacetimidate or acetate as excellent leaving groups by the reaction with trichloroacetonitrile or acetic anhydride, respectively. The successive addition of Cnucleophiles mainly activated arenes, allyltrimethylsilane and trimethylsiloxyalkenes to the active trichloroacetimidate or acetate intermediates in the presence of Lewis acid gave the desired products through the formation of new C-C bond.…”
Section: Introductionmentioning
confidence: 99%
“…The successive addition of Cnucleophiles mainly activated arenes, allyltrimethylsilane and trimethylsiloxyalkenes to the active trichloroacetimidate or acetate intermediates in the presence of Lewis acid gave the desired products through the formation of new C-C bond. [14][15][16][17][18] We nd it interesting to apply the trichloroacetimidate and acetate coupling methods in the structure modication of methyl-3-(4chlorophenyl)-3-hydroxy-2,2-dimethylpropanoate (3) via C-C coupling with methoxybenzene derivatives. Thus, the reaction of the ester 3 with trichloroacetonitrile in presence of DBU in dichloromethane at 25 C for 2 h afforded the trichloroacetimidate 9.…”
Section: Introductionmentioning
confidence: 99%
“… 18–21 Earlier we described the reaction of O -phthalimidomethyl trichloroacetimidate and O -diphenylmethyl trichloroacetimidate with C-nucleophiles in the presence of TMSOTf to afford a series of N -substituted phthalimides, 20 and benzhydryl derivatives. 21 Also, we showed the preparation of a number of N-protected non proteinogenic α-amino acid esters using trichloroacetimidate or acetate coupling methods via C–C bond formation from the corresponding methyl 2-benzamido-2-hydroxyacetate and benzyl(methoxycarbonyl)(hydroxy)methylcarbamate substrates and C-nucleophiles. 22 …”
Section: Introductionmentioning
confidence: 99%